Use of DNA from bite marks to determine species and individual animals that attack humans. (7th January 2014) - Farley, Sean; Talbot, Sandra L.; Sage, George K.; Sinnott, Rick; Coltrane, Jessica
ABSTRACT During the summer of 2008, 6 documented attacks and close encounters with brown bears (Ursus arctos) occurred in the greater Anchorage, Alaska (USA) area. We discuss findings from 2 incidents in which people were mauled within 2 km of each other over a 6‐week period and in which it was assumed that a single animal was responsible. To ensure public safety, authorities killed a brown bear implicated in the attacks by circumstantial evidence, though it was not known a priori that the animal was responsible. We extracted DNA from hairs and bite sites on the clothing of both victims and determined species and individual identity of the animal(s) involved in both incidents. Genetic data indicated the brown bear killed by authorities was responsible for one of the maulings, but not both. This research demonstrates that DNA‐based techniques, with appropriate sampling, can provide unambiguous identification of animals involved in attacks, as well as provide reasonable justification for excluding others. Because DNA‐based techniques can unequivocally identify individual bears carrying out attacks, they should be considered a standard method employed in wildlife attack investigations. © 2014 The Wildlife Society.